Assessing Drivers of Cross-Scale Variability in Peat Smoldering Combustion Vulnerability in Forested Boreal Peatlands - Wilkinson, Sophie L.; Moore, Paul A.; Waddington, James M. (Frontiers in Forests and Global Change, 2019)
Wildfire represents the largest areal disturbance of forested boreal peatlands and the spatial variability in the severity of these peat fires is both a leading source of uncertainty in boreal wildfire carbon emissions and a major challenge for regional wildfire management. Peat smouldering can emit large quantities of carbon and smoke to the atmosphere, and therefore can contribute to hazardous air quality. The wildland-industry interface and wildland-urban interface are both extensive across the sub-humid boreal plains (BP) ecozone where one-third of the area is covered by peatlands. As such, there is a growing research need to identify drivers of variability in smouldering combustion. This study uses hydrophysical peat properties to assess the drivers of cross-scale variability in peat smouldering combustion vulnerability in forested peatlands across the BP. Using a space-for-time chronosequence across the 120-year fire return interval and three main hydrogeological settings, and by incorporating hummock, hollow and margin locations, cross-scale variability is studied. We find that, based on peat properties such as specific yield (Sy) and gravimetric water content, forested peatland margins represent areas of high peat smouldering vulnerability, and that this is exacerbated with an increasing time-since-fire (stand-age). Although increasing Sy with time-since-fire in peatland middles may buffer water table drawdown, when accounting for increases in canopy fuel load, transpiration, and feather moss dominance forested peatland middles also become more vulnerable to smouldering combustion with time-since-fire. Moreover, the interaction of peatland margins with coarse- and heterogeneous-grained hydrogeological settings leads to lower Sy and higher density margin peat than in fine-grained settings, further increasing smouldering vulnerability. We estimate that forested peatland margins are vulnerable to combustion throughout their entire profile i.e. burn-out, under moderate-high water deficits in the BP. Furthermore, we identify peatland margin: total area ratio as a driver of smouldering vulnerability where small peatlands that are periodically disconnected from regional groundwater systems are the most vulnerable to high total peat carbon loss. We suggest that these drivers of cross-scale variability should be incorporated into peatland and wildfire management strategies, especially in areas near the wildland-industry and wildland-urban interface.